The Consequences of Digitization and Challenges to Kosovar Magazines in the Era of Social Media - Bajçinca, Emira (Information & Media, 2024)
The spread of the Internet has radically affected the world of media. As the main source of information in the 21st century, it inevitably became the new home of the media. This transition was not just a copy-paste of existing content: instead, the media had to change their content during this transformation. This analysis will identify these changes and observe what is being offered to audiences by online magazines. It will explore how the content of online magazines differs from what was offered to an audience in the 20th century. The object of analysis is the Kosovarja magazine, which has been published since 1971. This magazine is now only available online and the package of the Python programming language was used to extract the data necessary for this activity. In addition, the magazine Hylli i Dritës is used as a case study to explore the reasons why some magazines have not managed to be reproduced in the online market. In order to understand the audience’s perception of these changes, a public opinion survey of 1,051 respondents was conducted for this study.
Keywords: audience; Kosovo; magazine; representation; social media